Use of CoO/ZnAl2O4 Catalysts and Microwaved Assisted in Vanillin Synthesis - Birhi, Damiana Nofita; Iftitah, Elvina Dhiaul; Warsito, Warsito (Jurnal Kimia Valensi, 2023)
Vanillin is a main component in vanilla, which is widely used in the industrial world. Market demand for vanillin extract continues to increase, while the availability of vanilla pods is decreasing. To overcome this problem, research on the synthesis of vanillin continues to be carried out and develops every year. This research aims to examine the conversion level and selectivity of the catalyst as well as microwave radiation efficiency usage in vanillin synthesis. Catalyst CoO/ZnAl2O4 was synthesized from CoO and ZnAl2O4 using the impregnation method, then analyzed using FTIR, XRD, and SEM-EDX. Vanillin synthesis was conducted in two steps, incorporating microwave usage at 120oC, underwent 30 minutes to be completed then followed by oxidation around 10- and 15-minutes involving nitrobenzene also 1%, 4%, and 7% of catalysts CoO/ZnAl2O4. The result showed that during 10 and 15 minutes, the selectivity value and various yield percentages for each time variation and catalyst loading of vanillin had been successfully 100% converted. The best result was obtained using CoO/ZnAl2O4 with 4% catalyst loading for 15 minutes. The selectivity value and yield percentages were 67.78% and 7.5%. A one-step vanillin synthesis with conventional reflux could also be a comparison. The reactions were done at 130oC for 2 and 3 hours with 4% catalyst loading.